2013
DOI: 10.1148/rg.332125124
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Monochromatic Spectral Imaging with Fast Kilovoltage Switching: Reduction of Metal Artifacts at CT

Abstract: With arthroplasty being increasingly used to relieve joint pain, imaging of patients with metal implants can represent a significant part of the clinical work load in the radiologist's daily practice. Computed tomography (CT) plays an important role in the postoperative evaluation of patients who are suspected of having metal prosthesis-related problems such as aseptic loosening, bone resorption or osteolysis, infection, dislocation, metal hardware failure, or periprosthetic bone fracture. Despite advances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(142 citation statements)
references
References 14 publications
(25 reference statements)
5
122
0
12
Order By: Relevance
“…This application makes it possible to obtain images as though they had been acquired with a monoenergetic high-energy beam, which would lead to reduction of metal artefacts caused by beam hardening. [5][6][7][8][9] In addition to monoenergetic reconstructions in DECT, dedicated MAR algorithms have become available for clinical practice in the past couple of years. MAR algorithms in both single-energy CT imaging [10][11][12][13][14] and DECT imaging 8,9 have been shown to reduce metal artefacts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This application makes it possible to obtain images as though they had been acquired with a monoenergetic high-energy beam, which would lead to reduction of metal artefacts caused by beam hardening. [5][6][7][8][9] In addition to monoenergetic reconstructions in DECT, dedicated MAR algorithms have become available for clinical practice in the past couple of years. MAR algorithms in both single-energy CT imaging [10][11][12][13][14] and DECT imaging 8,9 have been shown to reduce metal artefacts.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Monoenergetic images, reconstructed from DECT data, have been shown to enhance the diagnostic value of CT images containing orthopaedic implants. [5][6][7][8][9][10] Li et al 12 studied the application of a commercially available MAR algorithm in radiotherapy treatment planning and concluded that it improved CT number accuracy and structure visualization in CT images of orthopaedic implants. However, the improvement in CT number accuracy was shown not to have any significant clinical impact on photon dose calculations.…”
mentioning
confidence: 99%
“…A monochromatic CT image can be useful in improving the visualization of a contrast agent and, as in this study, reducing metal-induced artefacts. 17 Filtered back projection (FBP) represents the current standard image reconstruction method, given its relative sensitivity to noise. Owing to Poisson statistics in X-ray imaging, lowering the dose by reducing the tube current may result in an unacceptable increase in image noise.…”
Section: Discussionmentioning
confidence: 99%
“…Beam hardening artifacts are minimized on high monoenergetic images (6). Beam hardening artifacts also arise from high attenuating implanted objects such as stents or pacing wires common in cardiovasSpectral detector CT for cardiovascular applications • 189 (6)(7)(8). Again, with SDCT, the spectral data necessary to create virtual high monoenergetic images is available by default if incidentally encountered artifacts interfere with image evaluation.…”
Section: Beam Hardening Artifactsmentioning
confidence: 99%